Technologies for restoring the OD matrix elements based on the results of processing video materials obtained from the quadcopters - R. Yakimov, Mikhail (International Journal of Engineering and Technology, 2018)
The article shows the technology of obtaining the initial data for modeling the movement of traffic and pedestrian flows on separate elements of the street-road network. The algorithm of automated calculation of traffic and pedestrian intensity based on the analysis of video data is given. The example of the city of Perm in Russia shows the technology of restoring the OD matrix elements based on the results of processing video materials obtained from the quadcopters.Â Â